Climate stressors and adaptation strategies using green stormwater infrastructure (GSI) systems in urban areas: Improving design and functionality - Ebru Özer; Berrin Tansel (City and Environment Interactions)
Climate stressors and their implications for stormwater management require evaluating climate-related threats and opportunities and implementing effective green stormwater infrastructure (GSI) systems to improve the resiliency and climate adaptation of communities, especially in urban areas. This study provides an evaluation of appropriate GSI systems that are aligned with specific climate conditions to analyze the relationship between climate types and the existing GSI practices; classify GSI implementation impediments; and identify appropriate GSI practices for different climate conditions. The existing GSI practices were critically analyzed as case studies in four different Köppen–Geiger climate regions, in view of their climate-specific GSI attributes. Our findings indicate that: (1) climate is an important factor in the design and implementation of GSI practices, and therefore, climate-specific factors need to be considered when designing effective GSI systems; (2) the implementation of climate-appropriate GSI practices can reduce climate-related stresses in communities; (3) utilizing combinations of different GSI systems improves their ability to function effectively across a wide range of climate conditions (i.e., climate events ranging from droughts to flooding); and (4) effective GSI practices can provide multiple benefits to communities (i.e., improved climate resiliency and adaptation to climate change, effective water and stormwater management practices).